Prevalence of Metatarsus Adductus in Patients Undergoing Hallux Valgus Surgery. (December 2014) - Aiyer, Amiethab A.; Shariff, Raheel; Ying, Li; Shub, Jeffrey; Myerson, Mark S.
Background: Metatarsus adductus (MA) is a congenital condition in which there is adduction of the metatarsals in conjunction with supination of the hindfoot through the subtalar joint. It is generally believed that MA precedes the development of hallux valgus. Historically, studies have demonstrated that patients with a history of MA were ~3.5 times more likely to develop hallux valgus. The purpose of this study was to identify the relative prevalence of MA in patients undergoing surgery for symptomatic hallux valgus. Methods: Between 2002 and 2012, 587 patients who underwent hallux valgus surgery were retrospectively identified following IRB approval and parameters including the hallux valgus angle (HVA), the intermetatarsal angle (IMA), and the metatarsus adductus angle (MAA) were recorded. The MAA was considered abnormal if the value was greater than 20 degrees. Interobserver and intraobserver reliability studies for the measurement of the MAA were completed as well. Results: Using the modified Sgarlato technique for measurement of the MAA, there was a high interobserver and intraobserver reliability. The interclass and intraclass coefficients were greater than .90. The prevalence of MA in this patient population was found to be 29.5%. Of those patients with MA, 23 males and 150 females were identified. This gave a male to female ratio of 1:6.5 ( P < .00001). Lesser toe deformities (claw toes, hammertoes) were the most commonly associated diagnoses identified. When stratified by severity, 113 (65%) patients had an MAA between 21 and 25 degrees, 41 (23.7%) had an MAA between 26 and 30 degrees, 8 (4.6%) patients had an MAA between 31 and 35 degrees, and 11 (6.3%) patients had an MAA greater than 36 degrees. Conclusion: Historically the prevalence of MA in patients with hallux valgus has been reported to be 35%. The data in this study indicate a comparable prevalence at 29.4%. The presence of concomitant MA may portend different outcomes for operative treatment of hallux valgus. Further research needs to delineate rates of persistence of deformity in this patient population to guide operative management. Level of Evidence: Level IV, case series.